THEORETICAL AND METHODOLOGICAL PROBLEMS OF THE DIGITAL AND INNOVATIVE ECONOMY AND CHINESE EXPERIENCE AND STRATEGIC DIRECTIONS IN THEIR SOLUTION - Qulmetov Mansurbek Ro'zmatovich; Sa’dullayeva Gulnoza Usmanovna (American Journals Publishing, 2024)
In the context of globalization, the rapid growth of the national economy of each country occurs primarily as a result of factors such as the digitization of the national economy, international trade, foreign investment and the improvement of financial services. As noted by the President on the digitization of the economy, “We need to develop a national concept of digital economy, which provides for the modernization of all sectors of the economy on the basis of digital technologies and on this basis, we need to implement the "Digital Uzbekistan - 2030" program". This article describes the theoretical and methodological problems of organizing a digital and innovative economy, the Chinese experience and strategic directions of solving them.
Keywords: Digital Economy, Economics, market economy, digital technology, digitization, robotics, IT, Digital Dividends, internet banking